2011
DOI: 10.18632/oncotarget.274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature induced by RNASET2, a tumor antagonizing gene, in ovarian cancer cells

Abstract: Using the Hey3Met2 human ovarian cancer cell line, we previously found the RNASET2 gene to possess a remarkable in vivo tumor suppressor activity, although no in vitro features such as inhibition of cell proliferation, clonogenic potential, impaired growth in soft agar and increase in apoptotic rate could be detected. This is reminiscent of the behavior of genes belonging to the class of tumor antagonizing genes (TAG) which act mainly within the context of the microenvironment. Here we present transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Therefore, although targeting of RNASET2 to P-bodies might suggest a rather general role in stress-induced RNA processing for this RNase, the results of this study suggest the occurrence of a sort of selectivity in target selection by this protein, although the mechanism ruling such putative selectivity are largely unknown. Our results thus, further confirm that the effects of RNASET2 on the cell transcriptome are more complex than expected, as already observed in previous investigations on the catalytically-dead RNASET2 protein (26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, although targeting of RNASET2 to P-bodies might suggest a rather general role in stress-induced RNA processing for this RNase, the results of this study suggest the occurrence of a sort of selectivity in target selection by this protein, although the mechanism ruling such putative selectivity are largely unknown. Our results thus, further confirm that the effects of RNASET2 on the cell transcriptome are more complex than expected, as already observed in previous investigations on the catalytically-dead RNASET2 protein (26).…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to our expectations, a great proportion of transcripts (both miRNAs and mRNAs) turned out to be downregulated rather than upregulated in the absence of RNASET2, thus, suggesting that the mechanism(s) by which this ribonuclease affects the expression level of several intracellular transcripts might not involve a direct cleavage of target RNAs. Of note, in a previous report microarray-based gene expression profiling of the Hey3Met2 ovarian cancer cell line showed that overexpression of a catalytically-dead RNASET2 protein could nevertheless affect the cell transcriptome significantly, suggesting that this protein can affect the cellular gene expression profile independently of its ribonucleolytic activity (26). These data are in keeping with several recent reports showing that proteins belonging to the T2 family members can affect several biological processes in a catalytically-independent manner (22).…”
Section: Discussionsupporting
confidence: 85%
“…Our research group has recently contributed to this issue by investigating the role of the human RNASET2 gene (10)(11)(12)(13)(14)(15). The latter codes for an extracellular RNase expressed in several tissues, including the ovary and tubal structures, and is highly conserved among phyla from viruses to humans, implying a crucial, evolutionary conserved function (16).…”
mentioning
confidence: 99%
“…Human RNASET2 is a glycoprotein encoded by the RNASET2 gene which is located on chromosome 6 (6q27) and demonstrated to be a tumor suppressor gene [16-20]. RNASET2 is the only member of the Rh/T2/S family of acidic hydrolases in humans [21] and shares 34% identity and 52% similarity with ACTIBIND (a fungal RNase T2).…”
Section: Introductionmentioning
confidence: 99%